Elaboration and validation of an ESL/EFL software evaluation instrument - Vládia Borges (Ilha do Desterro, 2011)
This study aimed at elaborating and validating an ESL/EFL software evaluation instrument that encompassed theprinciples of Communicative Language Teaching and aninteractive approach to computer use for language learning.Once the instrument was elaborated, it was tested for itsinternal consistency and inter-item and inter-rater reliability.The results of the Pearson Coefficient and the ICC Coefficientmeasures indicated high levels of inter-rater reliability for thegroup of 26 teachers. The Cronbach’s Alpha Coefficients for thethree programs indicated that the ESL/EFL software evaluationinstrument had adequate levels of inter-item reliability. Theseresults suggest that the ESL/EFL software evaluation instrumenthas high levels of internal consistency. These results indicate thatthe evaluation instrument has a high degree of reliability. Thepositive indicators of reliability obtained from the proceduresused to assess the inter-rater reliability and the internalconsistency and the face and content validity attributed tothe instrument suggest that the ESL/EFL software evaluation instrument is potentially valid for assessing the degree to whichESL/EFL software programs develop language skills accordingto the Communicative Language Teaching principles and aninteractive approach to computer use in language learning.